THE INFLUENCE OF SOCIAL MEDIA MARKETING AND BRAND IMAGE ON PURCHASING DECISIONS ON ERIGO STORE PRODUCTS - Sumarga, Hendi Eka; Rofiq, Iwan Setiawan; Yulianto, Franky Mahendra (Universitas Muhammadiyah Tangerang, 2024)
This study aims to analyze the influence of social media marketing factors (X1) and brand image factors (X2) on purchasing decisions (Y) for Erigo Store consumers in Tangerang City. This research is a quantitative research and survey research. The samples taken in this study were 100 respondents. Data obtained from distributing questionnaires. Primary data processing uses ms.excel and Statistical Package For Social Science (SPSS) version 25 as evaluation. While the data analysis used in this study includes: descriptive statistical analysis, classical assumption test, linear regression analysis, correlation analysis, coefficient of determination test and hypothesis testing. The results of this study indicate that the Social Media Marketing Factor (X1) and Brand Image Factor (X2) simultaneously have a positive and significant effect on Purchase Decision (Y) indicated by the Fcount>Ftable value of 319.453 > 3.09 with a significant value of 0.000 < 0.05..